DETERMINANTS OF CAPITAL STRUCTURE: A CASE OF NON-FINANCIAL SECTOR OF PAKISTAN - Urooj Khalid; Waqas Ahmad; Muhammad Abubakar; Muhammad Asrar (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2020)
The purpose of this study is to investigate the determinants of the capital structure of the Sugar Industry in Pakistan. This study reviews different theories related to the capital structure to formulate testable propositions concerning the determinants of the capital structure of the sugar industry of Pakistan. Panel data econometric techniques such as fixed effects and random effects are used to investigate the most significant factors that affect the capital structure choice of sugar firms listed on the Pakistan Stock Exchange for the period 2009-2018. The results of the study suggest that variables such as firm size, financial ﬂexibility, asset structure, profitability, liquidity, growth, risk, and affect all measures of the capital structure of Pakistan corporations. Short-term debt is found to represent an important financing source for corporations in Pakistan. Firm size and current ratio have a negative and significant relationship with Capital Structure ratios. Long term debt, Working Capital, Asset Structure, asset utilization, Effective tax rate, Financial Flexibility, Growth opportunity, Risk Volatility have a positive and significant relationship with Capital Structure ratios. Due to the existence of a negative relationship between profitability and capital structure, investors must consider capital structure before making investment decisions.